2010
DOI: 10.1186/1476-4598-9-283
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of head and neck cancer initiating cells through targeting glucose regulated protein78 signaling

Abstract: BackgroundHead and neck squamous cell carcinoma (HNSCC) is a highly lethal cancer that contains cellular and functional heterogeneity. Previously, we enriched a subpopulation of highly tumorigenic head and neck cancer initiating cells (HN-CICs) from HNSCC. However, the molecular mechanisms by which to govern the characteristics of HN-CICs remain unclear. GRP78, a stress-inducible endoplasmic reticulum chaperone, has been reported to play a crucial role in the maintenance of embryonic stem cells, but the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 61 publications
5
118
0
Order By: Relevance
“…In addition, the association of low ROS level and radioresistance in breast CSCs has been reported (16). Previously, we have successfully enriched a subpopulation of HN-CICs derived from both SAS and OECM1 HNSCCs (7,9). Herein, we first aim to understand whether the intracellular level of ROS is relatively lower in HN-CICs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the association of low ROS level and radioresistance in breast CSCs has been reported (16). Previously, we have successfully enriched a subpopulation of HN-CICs derived from both SAS and OECM1 HNSCCs (7,9). Herein, we first aim to understand whether the intracellular level of ROS is relatively lower in HN-CICs.…”
Section: Resultsmentioning
confidence: 99%
“…2D and E). Recent reports suggest that OSCC possess the potential of cancer stem cell (CSC) or the tumor initiating cell-like properties, and presents characteristics of aggressive tumor (22,26). Based on these studies as well as our finding that let-7d level is low in metastatic OSCC patients, we further explored the relationship between let-7d and cancer stemness properties of OSCC.…”
Section: Silencing Let-7d Enhances Mesenchymal Stem-like and Chemo-mentioning
confidence: 99%
“…After the bottom layer solidified, 2 ml of a top agar-medium mixture [DMEM, 10% (v/v) FCS, 0.3% (w/v) agar] containing 2x10 4 cells was added and incubated at 37˚C for 4 weeks. The plates were stained with 0.5 ml 0.005% crystal violet, and the number of colonies was counted using a dissecting microscope (26).…”
Section: In Vitro Cell Invasion Analysis and Soft Agar Assay The 24-mentioning
confidence: 99%
“…An increased expression of GRP78 protein has been reported in various cancers, including astrocytoma (10) and breast (11), gastric (12), lung (13), and prostate cancers (14). Further studies have revealed that the overexpression of GRP78 contributes to apoptosis inhibition, cancer progression, metastasis and angiogenesis, and confers a resistance to antitumor therapies (15)(16)(17). In addition, numerous studies have indicated that the IRE1/X-box binding protein 1 (XBP1) and PERK/eIF2α/ATF4 pathways are important in the promotion of tumor survival and growth under stress conditions (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…These pathophysiological conditions result in the disruption of the protein folding capacity and the buildup of unfolded and misfolded proteins within the ER, activating the UPR signaling pathway (5,6). Previous studies have demonstrated that the microenvironment of tumor cells resembles the physiologic ER stress, indicating that UPR plays an important role in cancer progression, malignancy and resistance to cancer therapy (15)(16)(17). Therefore, endogenous ER stress from the tumor microenvironment may contribute to the resistance of thyroid cancer cells to radiotherapy.…”
mentioning
confidence: 99%